PENGARUH PELAYANAN PRIMA TERHADAP KEPUASAN KONSUMEN PADA CV. GRIYA MANDIRI AGUNG, CITAYAM - Niken Herawati; Asrah Tandirerung Ranteallo; Titik Apriyani (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Property business is one of branch business was developed in indonesia. Property business in principle is one form of trade service. A company want to stay should have strategy in doing business, one of them was able to offer a best service. The method of this research is using observation, questionnaire, interview, and study documentation methods and the result of this research using analysis of the correlation coefficient, the test determination, justice and equality regression. The correlation coefficient result show 0,799 it means a positive relationship and have relations between service excellent and customer satisfaction, the determination obtained from the table summary significantly by 0,001 because fewer than of 0,05 the results of r square 0,639 or 63,9 % satisfaction and 36,1 % influenced by other factors. Calculation the regression equation obtained a significant degree of  0,001 where 0,001 > 0,05 so h1 accepted and h0 rejected this means that the significant regression, so the regression equation y = 13.662 + 0.682X. Then services in CV Griya Mandiri Agung Citayam must be improved .